Entrepreneurship : D & Z Frozen Food / Nur’azni Abu Shaari ... [et al.] - Abu Shaari, Nur’azni; Awang Teh, Rosnani; Ibrahim, Saifuddin; Bakeri, Nurbaidura; Abd Hamid, Zulfadly (2002)
Nowadays, our foods industries are expand from time to time. Many hotels and restaurants are developing each day and make a lot of profits from the business.